Fenomena Maraknya Kopi Angkringan di Era Milenial Sekarang - Wiratno, Esa; Fahirah, Raisah; Dalimunthe, Maulana Adinata (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This article aims to find out the reasons for the phenomenon of the rise of angkringan coffee in the current millennial era. The type of research used in this article uses qualitative research with a phenomenological approach. Based on the results of the observations made, the researchers found that the rise of angkringan coffee was caused by several factors. Among them, taking advantage of opportunities to run an angkringan business, caring for culture, being aware of the quality of coffee produced from the country, changing behavior and hanging out habits of millennials, community and social space. Keywords: Phenomenon, Millennials, Angkringan Coffee.